Delayed infection, family size and malignant lymphomas. Issue 12 (1st December 2000) - Vineis, P; Miligi, L; Crosignani, P; Fontana, A; Masala, G; Nanni, O; Ramazzotti, V; Rodella, S; Stagnaro, E; Tumino, R; Viganò, C; Vindigni, C; et al.
Abstract : BACKGROUND: The annual incidence of non-Hodgkin's lymphomas (NHL) is increasing by 3%–4% in different parts of the developed world. Excesses of NHL have been observed in populations exposed to immunosuppressants and to HIV, but these causes do not explain the increasing trends. It is suggested that delayed infection could explain NHL trends, through an impairment of the Th1/Th2 lymphocyte patterns. METHODS: In a population-based study on 1388 patients with NHL, 354 with Hodgkin's disease (HD) and 1718 healthy controls, the age of first occurrence of bacterial and viral diseases was investigated. Clinical records were perused in one centre to check the anamnestic data. FINDINGS: The age of occurrence of bacterial and viral diseases was significantly higher among NHL patients than in the controls. The association between later age at first bacterial or viral disease was limited to small families (OR= 1.95; 95% confidence intervals 1.26, 3.00, for age 4–8 at first infection; OR=1.91; 1.19, 3.06, for age 9+, compared with less than 4). The association was more obvious for bacterial diseases (possibly for the lower degree of misclassification). High grade lymphomas showed the strongest association. The later age of occurrence of bacterial or viral diseases in NHL patients is consistent with a higher incidence of lymphomas observed in higher social groups. No clear association was found between HD and age at first bacterial or viral diseases. INTERPRETATION: It is proposed that delayed infection could explain the increasing NHL trends, through an impairment of the Th1/Th2 lymphocyte patterns. The model of delayed infection has been proposed also to explain increasing prevalence rates of asthma.